Prevalence and antibiotic susceptibility of bacteria from acute and chronic wounds in Malaysian subjects - Wong, S.Y.; Manikam, R.; Muniandy, S. (Journal of Infection in Developing Countries, 2015)
Introduction: Chronic wounds represent a major health burden worldwide. It has been hypothesized that the polymicrobial nature of wounds plays an important role in their healing process. Thus, a review of pathogen frequency and susceptibility patterns in wounds is necessary to provide appropriate guidelines for antimicrobial usage. Methodology: In this study, microbiota and antimicrobial resistance in both acute and chronic wound patients treated at the University of Malaya Medical Centre, Malaysia, were compared. Wound swabs from 84 patients with acute wounds and 84 patients with chronic wounds were collected. The specimens were cultured using standard microbiological techniques. Isolates were then tested for antibiotic sensitivity with the broth microdilution method. Results: Of 210 pathogenic bacteria isolates, Staphylococcus aureus (49; 23.3%) and Pseudomonas aeruginosa (31; 14.8%) were the most prevalent bacteria found in wounds. Staphylococcus aureus was found significantly more often in patients with chronic wounds (41; 48.8%) than in patients with acute wounds (8; 9.5%), while Staphylococcus epidermidis was found predominantly in acute wounds (15; 17.9%). At the time of study, patients with chronic wounds (58.3%) had received more antibiotic treatments in the past previous 12 months compared with patients with acute wounds (16.7%). In the antibiotic susceptibility test, Staphylococcus spp. revealed highest resistance towards penicillin and ampicillin. Isolates showed no decrease in susceptibility against a number of newly developed antibiotics (linezolid, daptomycin, and tigecycline). Conclusions: Our finding showed that bacteria diversity and antimicrobial-resistant strains are more frequently found in chronic wounds than in acute wounds.